Permethrin induced arterial retention of native and oxidized LDL in rats by promoting inflammation, oxidative stress and affecting LDL receptors, and collagen genes - Feriani, Anouar; Tir, Meriam; Hachani, Rafik; Allagui, Mohamed Salah; Tlili, Nizar; Nahdi, Saber; Alwasel, Saleh; Harrath, Abdel Halim (Ecotoxicology and environmental safety, 2021)
This study is the first to examine the possible mechanism by which long-term exposure to permethrin (PER) can promote arterial retention of proatherogenic lipid and lipoproteins and related vascular dysfunction in rats. Experimental animals were administered two doses of oral PER, PER-1 (2.5 mg/kg/bw) and PER-2 (5 mg/kg/bw), for 90 consecutive days. The results indicated that both PER-1 and PER-2 increased plasmatic and aortic total cholesterol, low-density lipoprotein cholesterol (LDL-C), apo B-100, and oxidized LDL together with arterial scavenger LDL receptors (CD36) but markedly reduced plasmatic and hepatic high-density lipoprotein cholesterol and native LDL receptors in aortic and hepatic tissue. The levels of malondialdehyde, protein carbonyl, and reactive oxygen species were significantly higher, and glutathione content as well as catalase, superoxide dismutase, and glutathione peroxidase activities were suppressed in the aorta of the PER-1 and PER-2 groups. The arterial oxidative damage possibly caused by PER was clearly demonstrated by hematoxylin and eosin histological analysis. Moreover, PER treatment aggravated the inflammatory responses through enhancement of the production of proinflammatory cytokines (tumor necrosis factor–α, interleukin-2, and interleukin-6) in both plasma and aorta. Furthermore, PER-1 and PER-2 potentiated the dysregulation of the aortic extracellular matrix (ECM) content by increasing mRNA activation of collagens I and III. The abundant histological collagen deposition observed in the media and adventitia of intoxicated rats using Masson's trichrome staining corroborates the observed change in ECM. These data showed that oxidative stress related to PER exposure increases the arterial accumulation of lipoprotein biomarkers, likely by actions on both LDL and CD36 receptors, together with the disruption of the aortic ECM. •Permethrin (PER) increases oxidative stress.•PER induces arterial retention of lipoproteins and related receptors.•PER affected mRNA levels of type I and III collagen genes.•PER enhances the production of proinflammatory cytokines in both plasma and aorta.•PER increases neointimal formation and vascular stenosis.